Social values of sports movement and prevention of migrantophobia - Vladimir Alexandrovich Tarasov (Вестник Майкопского государственного технологического университета)
The modern world and Russia in particular is characterized by intensive migration processes. Ethnic, socio-cultural, religious conflicts and migrant-phobia are spreading in the countries that receive migrants. This requires a search for new means and mechanisms for the adaptation and integration of migrants, as well as the prevention of migrant phobia among the local population. The aim of the study is to give a sociological description of migrantophobia in Russia and substantiate the potential of the social values of the sports movement in its prevention. The content of the research is based on: 1) the analysis of bibliographic sources on the topic of the article; 2) a secondary analysis of sociological research on the perception of migrants and migrant phobia. Sociological studies demonstrate a downward trend in the level of migrantophobia in the Russian society, however, there is a need for new ways of preventing it. It has been concluded that sport as a social institution and such social values of sport as activity, self-realization, communication, respect, friendship, tolerance can play a significant role in the adaptation and integration of migrants, as well as in prevention of migrant phobia among the local population. Interpretations of the social functions of sports in relation to migrants have been given. The macro-, meso- and micro factors of the involvement of migrants in sports have been indicated.